Moden Vietnamese 3 Vietnamese for overseas vietnamese and foreigers - Phan Văn Giưỡng (Stage 3 students book with 2 CDS, 2009)
Giới thiệu về các mẫu texs; Grammar book; Book on vietnamese culture; Dictionaries.